The resources of adults taking care of their elderly parents at home – a research report - Bartnikowska, Urszula; Ćwirynkało, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Considering the increased demographic aging and system changes in the welfare system in Poland, home care became one of the most important forms of taking care of disabled or elderly persons. Although the country is rooted in the idea of a nanny state, based on large institutions and providing minimum income, for a long time now family has been considered as the basic provider of informal care to the elderly. The aim of the present study is to give some insight into the resources of adult children providing care to their elderly, disabled parents. In order to acquire a comprehensive perception of the phenomenon, the authors chose an interpretavist paradigm and applied a phenomenographic method. 21 participants, aged 41–65, who were caregivers of their parents, took part in semi-structured interviews. Two main research problems were formulated: (1) How do the participants perceive their resources as caregivers of their elderly, disabled parents? (2) What kind of support related to the care of their parents do they consider essential? Results: The participants distinguish two main kinds of resources: internal (e.g. values, passions, feelings for parents, economic situation) and external (e.g. parents, family, friends, professionals, medical equipment and centers they have access to). The narratives of the participants also indicate a number of needs they experience. Implications for practice are discussed.